Keeping Food Safe: Preparing and Cooking - Claudia Peñuela; Amarat Simonne (EDIS)
Food preparation and cooking can be fun and rewarding for many reasons. Well-prepared meals can save money and meet nutritional needs, and making safe and healthy meals a part of your lifestyle can contribute to lower healthcare costs. But many people with busy schedules find it difficult to make time to cook meals. And when we are rushed, we may not pay close attention to good food safety practices. It is very important to follow food safety guidelines during food preparation and cooking in order to reduce the risk of foodborne illness for you and your loved ones. Read this 3-page fact sheet to learn more about food safety during food preparation and cooking. Written by Claudia Peñuela and Amarat Simonne, and published by the UF Department of Family, Youth and Community Sciences, March 2012.